(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the processes of transition of the People’s Republic of China to the stage of socialist construction under Mao Zedong. In particular, domestic political struggles, abandonment of the "new democratic" path, radical turns in the socio-political direction of the Chinese Communist Party and constitutional reforms are covered. The study examines the impact of these processes on Chinese society and the public administration system from a scientific perspective.